Nomophobia dan Pengukuran: Tinjauan Literatur - M. Revo Artmando Lindani; TA Larasati; Chicy Widya Morfi; Winda Trijayanthi Utama (Universitas Malahayati, 2026)
ABSTRACT Nomophobia (no mobile phone phobia), is an anxiety disorder as well as fear that arises when a person cannot use his or her Smartphone. Based on the DSM IV guidelines, nomophobia belongs to a specific category of phobias characterized by a significant and exaggerated anxiety response to specific situations. The term